2002
DOI: 10.1080/00288330.2002.9517118
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of palytoxin‐like compounds by shellfish fedOstreopsis siamensis(Dinophyceae)

Abstract: Greenshell TM mussels (Perna canaliculus Gmelin), scallops (Pecten novaezealandiae

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 15 publications
0
53
0
2
Order By: Relevance
“…When employing the reported mouse lD50 values ranging between 0.15 -0.72 μg/kg b.w. (Munday, 2006;Rhodes et al, 2002;Riobo et al, 2008), the MU as observed with the 17 g mice employed by (Alcala et al, 1988) would be equal to 2,55 -12,24 ng PlTX/mouse. Using this range and the approximate 77 MU/g crab tissue, the Pltx concentration in the crab would have been approximately 196-942 ng/kg crab tissue.…”
Section: Pectenotoxin Poisoning (Pep)mentioning
confidence: 79%
“…When employing the reported mouse lD50 values ranging between 0.15 -0.72 μg/kg b.w. (Munday, 2006;Rhodes et al, 2002;Riobo et al, 2008), the MU as observed with the 17 g mice employed by (Alcala et al, 1988) would be equal to 2,55 -12,24 ng PlTX/mouse. Using this range and the approximate 77 MU/g crab tissue, the Pltx concentration in the crab would have been approximately 196-942 ng/kg crab tissue.…”
Section: Pectenotoxin Poisoning (Pep)mentioning
confidence: 79%
“…The differences (squares) between ostreocin-D and palytoxin are reported in the inset from the benthic dinoflagellate Ostreopsis siamensis which also produce PTX and ostreocin D (42-hydroxy-3, 26-didemethyl-19, 44-dideoxypalytoxin) (Fig. 4), a PTX analog (Rhodes et al 2002;Taniyama et al 2003;Ukena et al 2001;. Recently, PTX and a new analogue, Ovatoxin-a have been identified in the Mediterranean Sea during a massive bloom of the dinoflagellate Ostreopsis ovata (Ciminiello et al 2006;Ciminiello et al 2008).…”
Section: Palytoxinsmentioning
confidence: 99%
“…lethal dose ( LD 50 ) of PlTX in mice range from 150 to 720 ng/kg body weight (b.w.) (Onuma et al, 1999;Rhodes et al, 2002;Riobó et al, 2008).…”
Section: Mouse Bioassaymentioning
confidence: 99%
“…administration in mice with reported LD 50 values ranging between 0.15 and 0.72 μg/kg b.w., with the latter value determined according to OECD Guideline 425 (Munday, 2006;Rhodes et al, 2002;Riobó et al, 2008). In rats, the 24 hour-LD 50 was 0.63 µg/kg b.w.…”
Section: Toxicity Following Intraperitoneal (Ip) Administrationmentioning
confidence: 99%